Accountability of Governance and Sustainable Development Goals (SDGs) on Economic Growth in Village Fund Management According to the Perspective of Islamic Economics - Kharisma Nurul Fadhilah; Tulus Suryanto; Ahmad Hazas Syarif (Jurnal Indonesia Sosial Sains, 2025)
The purpose of this research is to investigate responsibility in the management of village funds from an Islamic viewpoint., covering the phases of preparation and execution, administrative record-keeping, and answerability reporting. This analysis aims to utilizes a qualitative descriptive approach approach using a case study method conducted in Sinar Rejeki Village, Jati Agung District, South Lampung Regency. The results suggest that the duty of overseeing village financial resources in Sinar Rejeki Village aligns with the regulations According to the Regulation of the Minister of Home Affairs No. 114 of 2014 and adheres to applicable Sharia principles. Therefore, based on egulation No 113 of 2014 from the Minister of Home Affairs, the Management of village funds planning in Sinar Rejeki Village is considered transparent and promotes active community participation.